A Statistical Analysis of the GDP and PCI of Bangladesh for the Coming Years - Md Arman (Research Synergy Foundation, 2023)
The objective of this paper is to anticipate Bangladesh's economic future and predict sustainability by looking at the GDP and per capita income (PCI) figures. Since the nation's independence, statistics spanning 51 years have been taken into account to track its development, and data spanning the last 11 years have been used to anticipate the years to come. In this study, annual statistics from 1971 to 2022 were studied to forecast the upcoming years. The result manifests a slow but sustainable development in the country's growth with some fluctuations. Analyzing the GDP and PCI insights into the continuous growth and development of Bangladesh. Sustainable development is not only economic development but also balancing the economic, social, and environmental factors to ensure that the development will sustain in the long run and benefits everyone. The results illustrate a surprising picture of the future. The information comes from the World Bank, OCED, and Asian Development Bank's National Account Data. The Least Square Method and the Trend Projection Method, a variant of the linear regression technique, are used in the current study to evaluate data and predict future trends. According to the IMF, the globe will experience a severe recession-like situation in 2023. In order to anticipate Bangladesh's economic status, the current study uses GDP and PCI. GDP has expanded since 1971 on average at a rate of 4.4%, whereas PCI has grown on average at a 1.8%.